Aktivitas Antioksidan Ekstrak Etanol Daun Ubi Jalar Ungu (Ipomea batatas L.) Hasil Budidaya Daerah Saree Aceh Besar - Sulastri, Sulastri; Erlidawati, Erlidawati; Syahrial, Syahrial; Nazar, Muhammad; Andayani, Thursina (Jurnal Rekayasa Kimia & Lingkungan, 2013)
This research was aimed to investigate the antioxidant activity of purple sweet potato leaves cultivated in Saree, Aceh Besar. The study was conducted in two stages. The first stage included sampel preparation, phytochemical test, max determination, testing of antioxidant activity by reducing power method, and TLC analysis. In stage 2 purification using column chromatography, phytochemical test, and antioxidant activity test were performed. The sample was dissolved by using 70% ethanol and 1.5 N HCl with a ratio of 85:15 (v/v). Phytochemical test results showed that the sample consisted of not only flavonoids but also tannins. The Rf value for both sample and standard are respectively 0.55 and 0.61 with absorbance value of 0.826 and 0.845. The sample was then purified using column chromatography and 25 fractions were grouped based on the color intensity abbreviated as FA, FB and FC. Photochemical test was then conducted to examine the purity of obtained fraction and FB was found to be relatively purer than other fractions. Reducing power test of FB with variation of weight 10 mg, 20 mg, 30 mg, 40 mg, and 50 mg gave the percentage inhibition 64.1, 6.7, 67.9, 70.3 and 73.6, respectively, while the percentage value of - tocopherol at simmilar weight variation are 32.1, 36.7, 43.5 and 50.2%. From the result obtained, it can be concluded that the antioxidant activity of ethanol extract of thick purple sweet potato leaves is higher than -tocopherol.Keywords: antioxidant activity, purple sweet potato leaves, reducing power